Optimization and mathematical modeling of green solvent-mediated extraction of essential oil from Citrus hystrix DC. leaves - Abdul Halim, Noor Amirah (2022)
Citrus hystrix DC. leaves or Kaffir lime leaves is known for its prominent organoleptic properties and therapeutical functionalities but are still underutilized as a source for the high-demand citrus-based essential oil (EO), due to the limitation of conventional hydrodistillation (HD) method that results in low yield. Green solvents such as natural deep eutectic mixture and subcritical-phase water described in previous studies not only improved the bioproduct extraction but also friendlier to the environment. However, the use of a natural deep eutectic solvent (NADES) requires correct formulation to be effective, while adopting water at subcritical conditions can affect the quality of EO. Hence, in this work, the application and the effectiveness of natural deep eutectic solventassisted hydrodistillation (NADES-HD) and subcritical water extraction (SWE) methods were comparatively studied. Based on screening and optimization studies, NADES-HD and SWE techniques successfully improved the EO yield by twice (1.32% w/w), and almost fourfold (2.14% w/w) respectively, in comparison to conventional HD (0.57% w/w) at their corresponding optimum extraction conditions. Both methods were well-fitted to the onesite kinetic desorption model at an extraction rate (k) of 0.0107 to 0.0136 min-1 and 0.0224 to 0.0463 min-1 for NADES-HD and SWE, respectively. Assessment of the mass transfer behavior estimates that the effective diffusivity, (D) values for NADES-HD and SWE corresponded to 3.68 x 10-6 to 5.59 x 10-6 cm2/s and 8.91 x 10-8 to 1.47 x 10-7 cm2/s, respectively, and obeys the Fick’s second law of diffusion. Meanwhile, for thermodynamics behavior, both methods were identified as exergonic and spontaneous processes with the free Gibbs energy (ΔG) values ranging from 6.83 to 8.73 kJ/mol for NADES-HD and 2.23 to 4.74 kJ/mol for SWE. The chemical profile analysis revealed that the SWE produced more EO compounds, where isopulegol (52.21%) was the predominant constituent, meanwhile NADES-HD has yielded EO that is rich in citronellal (75.99%), similar to conventional HD (75.04%). Besides, SWE-extracted EO exhibited a superior antioxidant activity while the EO extracted by NADES-HD demonstrated a better antimicrobial activity. The physical characterization of the post-extraction leaves samples indicated that the lignocellulosic structures of SWE-extracted leaves were severely disrupted compared to the damages observed on NADES-HD and conventional HD samples, hence implying the reason for the higher EO yield obtained by the SWE process. In brief, NADES-HD and SWE are the potential alternatives to conventional HD, where the quantity and quality of EO could be enhanced within a shorter extraction time and at the same time could minimize the energy requirement.